Game-based educational experience in clinical simulation and academic achievement in medical students: a retrospective study - Maria Amalia Salafia; María Elena Perez-Ochoa (BMC Medical Education)
Abstract Background In recent years, medical education has increasingly embraced gamification as a method for teaching clinical skills. In Peru, social isolation resulting from the COVID-19 pandemic forced universities and academic institutions to restructure their teaching methods, while there are no reports about the impact of this strategies in Peruvian students. In this study we evaluated the feasibility and patterns of use of a novel video game based didactic activity in undergraduate students from a School of Medicine in Peru. Method We conducted a retrospective pilot study in medical students who used the Full Code Medical Simulation platform. We retrieved scoring data obtained from this platform for selected cases of clinical courses with an appropriate number of users [clinical medicine (CM) I (7 cases), CM II (17 cases), surgery I (6 cases) and surgery II (6 cases)]. cases)]. We also evaluated patterns of use and the association between academic performance and the Full Code scores. Results A total of 590 students were included in the study. We found a direct correlation between the student’s course grade and Full Code score in all courses (CM I: p < 0.001, CM II: p < 0.05, Surgery I: p < 0.05 and Surgery II: p < 0.05). CM II course students who dedicated more time to completing cases received better grades (p < 0.05). The pattern of use of Full code were similar in students regardless their academic performance. In addition, students with higher academic performance were more likely to have higher scores in the platform (p < 0.001). Conclusion The use of gamification in clinical simulation was highly feasible in students of medicine regardless their academic performance. Prospective and interventional studies are needed to assess if the Full Code platform directly affect the learning outcomes.